2016
DOI: 10.1111/idj.12223
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries and toothbrushing habits among preschool children in Khartoum State, Sudan

Abstract: Background: Dental caries in preschool children remains a major dental public health problem and affects significant numbers of children in developed and developing countries. The incidence is increasing in developing countries, such as Sudan, because of lifestyle changes, absence of oral health-preventive services and inadequate access to oral health care. Objectives: This study assessed the prevalence of dental caries and toothbrushing habits among 3-to 5-year-old preschool children in Khartoum State, Sudan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 22 publications
4
37
1
Order By: Relevance
“…An initial screening of the title and abstract revealed that 551 articles were duplicates and 1707 articles did not meet the inclusion criteria. Full texts of the remaining 152 articles were assessed, and 37 studies were included in the present study . No additional publications were identified from the bibliography of these 152 articles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An initial screening of the title and abstract revealed that 551 articles were duplicates and 1707 articles did not meet the inclusion criteria. Full texts of the remaining 152 articles were assessed, and 37 studies were included in the present study . No additional publications were identified from the bibliography of these 152 articles.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies conducted in the Middle East (Saudi Arabia and Turkey), one in Africa (Sudan), and one in Oceania (Australia) were included. Of the 37 publications, 28 were from countries/districts with high or very high HDI scores (HDI > 0.70), while only one publication was from a country with a low HDI score (HDI < 0.55) (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dental caries, one of the most common oral diseases, has been declining in developed countries. This is attributed to many factors, including better oral hygiene, improved dietary habits, effective use of fluorides, and oral health‐promotion programs . Nevertheless, dental caries remains epidemic and is widely prevalent in children, especially underprivileged ones in developing countries…”
Section: Introductionmentioning
confidence: 99%